BIODEGRADASI ZAT WARNA REMAZOL BLACK B SECARA AEROBIK- ANAEROBIK DALAM SISTEM BIOFILTRASI VERTIKAL DENGAN MENGGUNAKAN TANAMAN TALAS (Colocasia esculenta) - Hartesa W, Febby; Budiarsa Suyasa, I Wayan; Simpen, I Nengah (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2017)
PIGMEN BIODEGRADATION OF BLACK B REMAZOL ON AEROBIC- ANAEROBIC IN VERTICAL BIOFILTRATION SYSTEM USING TARO PLANT (Colocasia esculenta) The research was conducted to decrease concentration of remazol black b on vertical biosystem of Colocasia esculenta plant with and without addition of activated suspension as variable. The activated suspension was collected from many sources such as sediment of Badung river, Serangan river, Soputan river and dying waste treatment. The aims of this research are: 1) to determine the best activated suspension from seeding sample from some ecosystems, 2) to determine optimal time of vertical biosystem plant to decrease concentration of remazol black b, 3) to know effectivity and capacity of vertical biosystem plant to decrease concentration of remazol black b, TDS and TSS. The results of research show that best activated suspension was provided from sample Serangan river sediment, optimal time to decrease concentration of remazol black b with and without addition of activated suspension is 60 hours and 96 hours. The effectivity system with addition activated suspension to decrease concentration of remazol black b is 97,82% and capacity is 2,7963 ppm/m 3 hours. The effectivity system with addition activated suspension to decrease concentration of TDS is 83,93% and capacity is 14,44 ppm/m 3 hours. The effectivity on system with addition activated suspension to decrease concentration of TSS 89,75% and capacity is 9,1568 ppm/m 3 . The effectivity on system without addition activated suspension to decrease concentration of remazol black b is 89,35% and capacity is 2,5543 ppm/m 3 hours. The effectivity on system without addition activated suspension to decrease concentration of TDS is 65,71% and capacity is 11,31 ppm/m 3 hours. The effectivity on system without addition activated suspension to decrease concentration of TSS is 72,29% and capacity is 7,3746 ppm/m 3 hours.